Curar, prevenir y asistir: Medicina y salud en la historia chilena - María Soledad Zárate Campos (Centre de Recherches sur les Mondes Américains, 2014)
This article identifies and describes part of the bibliography available about history of medicine and public health related to Chile in the colonial and republican periods. The literature reviewed gathers studies produced by physicians and professional historians, commenting on the contributions in terms of topics and methodologies of both communities. Also, this study recognises analytical limits and some weaknesses of this historiography and suggests new questions for future research.